STRATEGI PENGEMBANGAN PASAR TRADISIONAL DALAM MENINGKATKAN KEPUASAN PEDAGANG - Rohmat Wahyudi (Jurnal Pengembangan Wiraswasta, 2019)
Traditional markets are a form of popular economy and are also one of the pillars of the national economy in Indonesia. The traditional market conditions are mostly dirty and uncomfortable to shop but still crowded by buyers.This study uses descriptive analysis method with a qualitative approach. The research location is Arriyad market, Mampang Prapatan, South Jakarta. The research sample was 60 traders from 289 traders.The results show that traditional market development is carried out by the market manager Arriyadh through traditional market revitalization aimed at increasing market competitiveness and reactivating traditional market activities in order to compete with the modern market. Analysis of market development strategies in increasing the satisfaction of traders in the Arriyadh market includes four aspects including social aspects, non-physical aspects, economic aspects and physical aspects. From the analysis of the four aspects the traders were not satisfied, because the system of follow-up complaints and suggestions were slow, facilities and infrastructure were not optimal and the welfare of traders in terms of income was not optimal (decreased). Keywords:Strategy, Traditional Market Development, and Trader Satisfaction